2003
DOI: 10.1021/bp034070w
|View full text |Cite
|
Sign up to set email alerts
|

Geranium Leaf Assisted Biosynthesis of Silver Nanoparticles

Abstract: Development of biologically inspired experimental processes for the synthesis of nanoparticles is evolving into an important branch of nanotechnology. In this paper, we report on the use of Geranium (Pelargonium graveolens) leaf extract in the extracellular synthesis of silver nanoparticles. On treating aqueous silver nitrate solution with geranium leaf extract, rapid reduction of the silver ions is observed leading to the formation of highly stable, crystalline silver nanoparticles in solution. Transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
512
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,062 publications
(554 citation statements)
references
References 36 publications
39
512
0
3
Order By: Relevance
“…No change in peak due to the excitations of SPR of nanoparticles indicates that nanoparticles are in spherical structure which was further confirmed by TEM image. Similarly, Shankar et al [14] reported that geranium leafassisted silver nanoparticles formed the SPR band at 440 nm due to the excitation of longitudinal plasmon vibrations.…”
Section: Discussionmentioning
confidence: 86%
“…No change in peak due to the excitations of SPR of nanoparticles indicates that nanoparticles are in spherical structure which was further confirmed by TEM image. Similarly, Shankar et al [14] reported that geranium leafassisted silver nanoparticles formed the SPR band at 440 nm due to the excitation of longitudinal plasmon vibrations.…”
Section: Discussionmentioning
confidence: 86%
“…But, nanotechnology is also a double-edged sword; although nanotechnologies can be used in many areas and many beneficial effects have been achieved, it also involves many adverse effects or unclear hazards to humans, animals, plants, and the environment. Government and regulatory authorities (regulatory agencies, certification bodies) as well as environmental, health and safety councils (such as Environment Health Services), non-governmental organizations, and scientific authorities all over the world are realizing the importance of nanotechnologies risk assessment (Vyom et al 2012), and have given their own suggestion, view, and guidance (USEPA 2007;RS/RAE 2004;COT-COM-COC 2005;Scenihr 2009;SCCP 2007;Dhawan et al 2011;FOE 2006).…”
Section: Potential Risks Of Nanotechnologiesmentioning
confidence: 99%
“…The silver nanoparticles have the ability to anchor to the bacterial cell wall and subsequently penetrate and followed by the disruption of ATP production and DNA replication, thereby causing structural changes in the cell membrane and death of the cell. Evidently report of some authors mentioned that there is the formation of "pits" on the cell surface when accumulating these nanoparticles on the cell surface (20)(21)(22)(23)(24) and causes damage to the microbes.…”
Section: Anti -Bacterial Activtymentioning
confidence: 99%